Transforming Health Care Through Research: Highlights From the 2025 Annual Conference of the Health Care Systems Research Network - Michael A. Horberg; Suzanne Simons (Journal of Patient-Centered Research and Reviews)
During this unprecedented time of uncertainty and disruption, the 2025 Annual Conference of the Health Care Systems Research Network (HCSRN) took place on April 8 to 10, 2025, in St. Louis, Missouri, at the Marriott St. Louis Grand. Nearly 265 participants from 19 HCSRN member institutions came together to network, collaborate, and connect at the conference, which featured the theme, “Optimizing Collaborations to Advance Health in a Dynamic Research Landscape.”